Kekejaman-penggunaan metafora dalam fotografi - Hii, Ung Kiong. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Photography is the consolidation oftechnology and art. It not just to record the definite world but it can be a complex work of art with meaning and messages. Video and photography medium was used to record and put forth the issues on animal's cruelty. The slaughtering and skinning visuals of the animals was used to ensure the effectiveness and to maximized the visual impact.